Teachers' Perceptions of Collaborative Learning Methods in Developing Children's Multiliteracies - Ningsih, Risa Wahyuni; Fajriyah, Lathifatul; Rizqiyani, Revina (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2025)
The research seeks to understand the perspectives of the educators regarding the use of pedagogical strategies of collaboration in the enhancement of the multiliteracies of children in the in the Al-Qur'an Bilingual Al-Azhar Kindergarten (TK). This study is based on the foundational understanding of the necessity of expanding the pedagogical practices used of in the early childhood education to include collaboration and multiliteracies in order to address the demands of the 21st Century. For this study, qualitative methods in the form of a field study were used in order to focus on understanding the experience of three study participants, a classroom teacher, and a teacher's aide, and a principal who were all purposefully selected. Data were collected through a combination of in-depth interviews and participatory observations and analyzed through the use of the interactive model of Miles and Huberman in order to engage in a series of data reduction, data display, and conclusion drawing. It was revealed in the findings of this study that the understanding teachers held regarding the notion of multiliteracies was primarily focused on the reading and writing that is foundational as opposed to the more complex visual, digital, and sociocultural factors. There is a presence of what is collaborative learning in practice, however, it is more closely aligned with the notion of group learning rather than collaboration that embodies the sharing of responsibilities in social construction of knowledge and meaning. The main issues were a deficit in pedagogical knowledge, absence of instructional training, insufficient pedagogical training, and unavailability of time. The research suggests that to best implement multiliteracy-based collaborative learning in early childhood education, teachers should gain a deeper understanding of multiliteracies in a pedagogical context, which is best obtained through ongoing professional development, and collaborative and pedagogical thinking that is ongoing and reflective in structure.